2016
DOI: 10.1111/jopr.12473
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Core/Veneer Thickness Ratio and Cyclic Loading on Fracture Resistance of Lithium Disilicate Crown

Abstract: Purpose: To investigate the effect of core/veneer thickness ratio on the fracture strength of lithium disilicate crowns subjected to cyclic loading in a simulated oral environment. Materials and Methods: A typodont molar tooth received a standard complete crown preparation according to the manufacturer's instructions. Sixty lithium disilicate crowns were prepared and assigned to three groups with the following core/veneer thickness ratios A: 0.7 (0.6/0.9), B: 1.1 (0.8/0.7), and C: 2 (1.0/0.5). The cores were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Also, in a finite element study, Yucel et al 27 demonstrated different stress distributions on the restoration, depending on the abutment materials; when a restoration was attached to dentin and epoxy resin die, the distribution of stresses was similar, but that was different when the restoration was bonded to a metal die. 27 Therefore, epoxy resin material has been used in several previous studies [28][29][30][31][32][33] as a simulation of the natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a finite element study, Yucel et al 27 demonstrated different stress distributions on the restoration, depending on the abutment materials; when a restoration was attached to dentin and epoxy resin die, the distribution of stresses was similar, but that was different when the restoration was bonded to a metal die. 27 Therefore, epoxy resin material has been used in several previous studies [28][29][30][31][32][33] as a simulation of the natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that the thermomechanical cycling test in water did not significantly affect restoration strength, insofar as the mean fracture load values between the same CVT ratios were not significantly different. Previous studies on bilayered systems have reported similar results . One explanation for these results lies in the possibility that the zirconia core was veneered, and, hence, did not come into direct contact with the chewing forces; therefore, the veneering ceramic may have acted as a protective layer .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on bilayered systems have reported similar results. 36,39 One explanation for these results lies in the possibility that the zirconia core was veneered, and, hence, did not come into direct contact with the chewing forces; therefore, the veneering ceramic may have acted as a protective layer. 31 Furthermore, the degradation mechanism is usually very slow in oral temperatures, and this may lead to a significant decrease in the strength of dental restorations over periods of several decades of wear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations